2010
DOI: 10.1021/es100828u
|View full text |Cite
|
Sign up to set email alerts
|

A Downhole Passive Sampling System To Avoid Bias and Error from Groundwater Sample Handling

Abstract: A new downhole groundwater sampler reduces bias and error due to sample handling and exposure while introducing minimal disturbance to natural flow conditions in the formation and well. This "In Situ Sealed", "ISS", or "Snap" sampling device includes removable/lab-ready sample bottles, a sampler device to hold double end-opening sample bottles in an open position, and a line for lowering the sampler system and triggering closure of the bottles downhole. Before deployment, each bottle is set open at both ends t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…As such, they are well suited for determining depth‐discrete concentrations within a well. Several other grab‐sample devices have been developed and tested extensively, including in situ sealed samplers (i.e., Snap Samplers) (ITRC 2007; Parker and Mulherin 2007; Britt et al 2010). Extensive technical and regulatory guidance has been published, including the results of comparative validation studies.…”
Section: Introductionmentioning
confidence: 99%
“…As such, they are well suited for determining depth‐discrete concentrations within a well. Several other grab‐sample devices have been developed and tested extensively, including in situ sealed samplers (i.e., Snap Samplers) (ITRC 2007; Parker and Mulherin 2007; Britt et al 2010). Extensive technical and regulatory guidance has been published, including the results of comparative validation studies.…”
Section: Introductionmentioning
confidence: 99%
“…They use vials introduced into the well in order to avoid volatilization of sampled compounds. One of these devices was compared with sampling at low flow rate after a purge and with PDB on six sites contaminated with volatile organic contaminants [9]. This study showed a good correlation between data obtained with the three methods.…”
Section: Introductionmentioning
confidence: 92%
“…Brite et al 23 have described a downhole groundwater sampler to reduce bias and error due to sample handling and exposure while introducing minimal distribution to natural flow conditions in the formation and well. This in situ sealed (ISS) or "snap" sampling device includes removable/flab-ready sample bottles, a sampler device to hold double end-opening sample bottles in an open position, and a line for lowering the sampler system and triggering closure of the bottles downhole.…”
Section: Sampling Devicesmentioning
confidence: 99%